The effect of low-temperature structural relaxation on free volume and chemical short-range ordering in a Au49Cu26.9Si16.3Ag5.5Pd2.3 bulk metallic glass. (1st July 2015) - Evenson, Zach; Koschine, Tönjes; Wei, Shuai; Gross, Oliver; Bednarcik, Jozef; Gallino, Isabella; Kruzic, Jamie J.; Rätzke, Klaus; Faupel, Franz; Busch, Ralf
Abstract : Structural changes due to low-temperature relaxation in a Au49 Cu26.9 Si16.3 Ag5.5 Pd2.3 bulk metallic glass are investigated with a combination of positron annihilation lifetime spectroscopy (PALS) and high-intensity synchrotron X-ray scattering. The free volume content of the glass remains unaffected during annealing at 50 °C while distinct changes in the chemical short-range order occur on a nearest-neighbor length scale of ∼3 Å. A highly localized process of atomic rearrangement is envisioned, which may help to understand the microscopic origin of the β -relaxation.